Temperature variation linked to trellis height: an opportunity for adaptation to climate change? - Laure de Rességuier; Philippe Pieri; Théo Petitjean; Séverine Mary; Cornelis van Leeuwen (IVES Technical Reviews, 2023)
Temperature is a key factor in vine growth and grape composition (Jones, 2006). Climate change is already having an impact on these parameters in many wine regions, and it is becoming necessary to adapt in order to continue producing quality wines, without strongly altering their typical character (van Leeuwen et al., 2019). One way to adapt could be to modify the vine’s training system. A study of temperature at different heights was carried out in the Bordeaux region to assess whether increasing trunk height could modify the microclimate in the bunch zone (de Rességuier et al., 2023).